Planning System and Its Driving Forces: A New Institutionalist Prespective - Delik Hudalah (The Institute for Research and Community Services, Institut Teknologi Bandung, 2006)
While focused on exploring critically how precious studies explain the relation between planning system and broader societal context, the concept of planning system itself is describe comprehensively in this paper. Planning system is not regarded as an independent phenomenon but more as product of the embedded institutional-cultural forces and influenced by globalizing neo-liberal ideas, which strengthen the existence of policy transfer. It is argued that the policy makers should pay more critical attention on the later since it may potentially attack the effectiveness of planning policy irrespective on the established domestic planning culture. Besides, understanding how the institutional process influences the development of planning systems in developing and transitional countries will be becoming a big homework that the researchers have.